2012
DOI: 10.1007/s11064-012-0814-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Specific Gene Expression and Editing Responses to Chronic Fluoxetine Treatment in the In Vivo Mouse Brain and Their Relevance for Stress-Induced Anhedonia

Abstract: Recently developed methods for fluorescence-activated cell sorting (FACS) of freshly-isolated brain cells from transgenic mice combining fluorescent signals with cell type-specific markers allow cell-type separation. Based upon previous observations in primary cultures of mouse astrocytes we treated transgenic mice tagged with a neuron-specific or an astrocyte-specific marker with fluoxetine, either acute (10 mg/kg for 2 h) or chronic (10 mg/kg daily for 2 weeks). Acute treatment upregulated cfos and fosB mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 51 publications
6
74
0
Order By: Relevance
“…Characteristics, usage and advantages of these cultures has recently been authoritatively reviewed (Lange et al, 2012). Ontogenetic similarity with freshly isolated astrocytes in gene development has been reported by ourselves (Li et al, 2012b); similarly there is evidence for identical drug-induced changes in gene expression between in vitro and in vivo assessed astrocytes (Li et al, 2012a; Song et al, 2012). …”
Section: Methodssupporting
confidence: 73%
“…Characteristics, usage and advantages of these cultures has recently been authoritatively reviewed (Lange et al, 2012). Ontogenetic similarity with freshly isolated astrocytes in gene development has been reported by ourselves (Li et al, 2012b); similarly there is evidence for identical drug-induced changes in gene expression between in vitro and in vivo assessed astrocytes (Li et al, 2012a; Song et al, 2012). …”
Section: Methodssupporting
confidence: 73%
“…Nor are our cultures similar to those used previously by Harold Kimelberg (Hertz et al, 1985). Recently we have compared expression of genes of interest in specific studies in freshly isolated astrocytes and these cultured astrocytes and consistently shown similar expression of several different genes for acid extruders, other transporters and glutamate receptor subtypes (Fu et al, 2012; Li et al, 2012a,b; Song et al, 2012). The gene expression of Na + ,K + ATPase subtypes in freshly isolated cells which was shown in Figure 5 is also identical to that previously shown in these cultures (Peng et al, 1997, Under revision).…”
Section: Consistent and Supplementary Observations In Cultured Cellsmentioning
confidence: 87%
“…Use of astrocyte cultures has recently been authoritatively reviewed (Lange et al, 2012), and in our own cultures drug-induced changes in gene expression and editing have recently been confirmed in freshly isolated cells from mice treated with the same drugs (Li et al, 2012b; Song et al, 2012; Peng et al, 2013). Moreover the development of the glutamate/aspartate exchanger component aralar shows similar developmental patterns in the two preparations, with an increase in the cultured cells after dBcAMP administration (Li et al, 2012a). …”
Section: Methodsmentioning
confidence: 94%
“…MPEP is generally known as an inhibitor of mGluR5, a metabotropic glutamate receptor, but this receptor is only functioning in astrocytes during very early development (Sun et al, 2013). MPEP appears also to inhibit the kainate receptor GluK2, present in mature astrocytes in vivo (Li et al, 2012a) and active in culture (Li et al, 2011). GluK2 is equally distributed in freshly isolated neurons and astrocytes (Li et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation